The excommunication of Elizabeth I : faith, politics, and resistance in post-Reformation England, 1570-1603 - Muller, Aislinn (St. Andrews studies in Reformation history., 2020)
In The Excommunication of Elizabeth I, Aislinn Muller examines the excommunication and deposition of Queen Elizabeth I of England by the Roman Catholic Church, and its political afterlife during her reign. Muller shows that Elizabeth's excommunication was a crucial turning point for both Catholics and Protestants, one that irrevocably changed attitudes towards the queen, widened political participation and resistance, and posed a destabilising threat to her regime. The Excommunication of Elizabeth I demonstrates how this event exacerbated religious tensions in England's foreign and domestic politics, and how Elizabeth's conflict with the papacy shaped the development of anti-Catholicism in post-Reformation England.